Integrated Pest Management of Important Insect Pests of Coconut - Winotai, Amporn (International Coconut Community, 2014)
IPM or Integrated pest management is a strategy that integrates various methods of cultural, physical, mechanical, biological control and selection of pesticides as the last option. IPM is not only cost effective but simultaneously prioritized human and environmental safety. IPM is based on farmer’s local knowledge, acceptance and education. Several insects were reported as coconut pests in Asia and Pacific region. Among these pests, rhinoceros beetle, red palm weevil, coconut hispine beetle, coconut black headed caterpillar and coconut scale currently causing severe damage to coconut palms in the region. Rhinoceros beetle, Oryctes rhinoceros Linnaeus (Coleoptera: Scarabaeidae) is native to South Asia and Southeast Asia. Management of this pest is a combination of sanitation in plantations and surrounding, biological control by using Metarhizium anisopliae, Oryctes virus and pheromone trapping. Red palm weevil, Rhynchophorus ferrugineus Olivier (Coleoptera: Curculionidae) outbreaks usually occur after infestation of rhinoceros beetle. Keeping the rhinoceros under control results in keeping the red palm weevil under control too. Pheromone trapping is also developed for reduction of this pest. Coconut hispine beetle, Brontispa longissima (Gestro) (Coleoptera: Chrysomellidae), is an invasive pest occurs in Southeast Asia and Pacific region. Biological control of the pest is recommended by releasing two species of parasitoids, Asecodes hispinarus Boucek (Hymenoptera: Eulophidae) and Tetrastichus brontispae Ferriere (Hymenoptera: Eulophidae). Coconut black headed caterpillar, Opisina arenosella Walker (Lepidoptera: Oecophoridae) is one of the key pests of coconut in South Asia and invaded Thailand in 2008. Management of this pest in its native region consisted of: 1) removing and burning of the infested leaves; 2) biological control by releasing parasitoids such as Goniozus nephantidis (Muesebeck), Bracon brevicornis (Wesmael), Brachymeria nephantidis Gahan; and 3) chemical control by trunk injection and applying systemic insecticides in the holes. Bacillus thruringiensis has been recommended for biological control of the black headed caterpillar in Thailand. Coconut scale, Aspidiotus destructor Signoret (Hemiptera: Diaspididae) has been reported as a serious in Philippines. Predators are significant biological control agents in limiting A. destructor populations. The most common natural enemies associated with the coconut scales are the coccinellid beetles Chilocorus spp., Azya trinitatis, Cryptognatha nodiceps, Rhyzobius lophanthae and Pentilia castanea. Local parasitoids, Comperiella, Aphytis and Encarsia also play important roles in keeping the pest under control. Application of insecticides could inducee the infestation of the scale. Biological controls is recommended for suppression of other coconut pests, such as slug caterpillars (Lepidoptera: Limacodidae) such as Parasa lepida Cramer; coconut leaf moth, Artona catoxantha Hampton (Lepidoptera: Zygaenidae); and coconut leafminer, Promecotheca cumingii Baly (Coleoptera: Chrysomelidae).